Valuasi Saham Perusahaan Teknologi: Studi Kasus Di Perusahaan Teknologi Yang Terdaftar Pada Indeks Idxtechno - Muhammad, Reza Fahmi (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2024)
This research aims to discuss the research of stocks in the technology sector (IDXTECHNO) with an emphasis on in the Indonesia Stock Exchange (IDX), the stock fundamental analysis of which listed in IDXTechno. This research covers economic factor, industrial factor, and company factors, finalized with valuation of stock using the relative valuation method and discounted cash flow. This research is done as a response to the phenomenon of technology company stock's surge of price in the IDX which are potentially caused by asset overvaluation and herding behavior. The irrational investor decision might cause the price of an asset incredibly high and potentially caused an economic bubble. This research is a study case model which use one of the companies listed in the IDX techno as a valuation sample. This research aims to find out whether the market price of the companies listed in the IDX techno is overvalued or undervalued. Furthermore, the research also aims to detect a potential herding behavior from the price surge in the IDXTECHNO between 2021 to the 2024.